The Effect of Attitude and Economic Foundations on Criminal Policy Making in the Field of Intellectual Property - Melika Khalilollahi; Mohsen Sadeghi; Shahla Moazami (پژوهشهای حقوقی)
Today, the traces of intellectual property rights can be seen in all fields. On the other hand, the economy has long been necessary for the progress and continuity of a country. Intellectual property rights have a direct and indirect relationship with economic growth and development, with efficient and appropriate laws in this field, it can be seen in different sectors. Therefore, the aim of this research is to analyze and investigate the effect of economic attitude and fundamentals on criminal policies in the field of intellectual property rights (in a qualitative way) and to answer the question that economic attitude and fundamentals affect the optimal criminal policy in What kind of appropriate and efficient punishment does this area need? The hypothesis of the research is that the nature of intellectual property crimes is such that it seems that the punishment of monetary penalty and also the consideration of punitive damages is more efficient than the punishment of imprisonment, and according to some evidence, the punishment of imprisonment cannot be efficient and useful, in other words, the costs of the crime should be also considered. This research is based on documentary and field methods in the form of interviews with the benefit of library resources and so on. Also, this research shows that in the case of determining the punishment of imprisonment, a criterion should be determined based on the type of crime, based on the conditions, and considering various factors for the criminal.